Globalization and becoming nation subjectivity, nationhood, and narrative in the period of global capitalism - Gonzaga, Elmo; Hagedorn, Jessica Tarahata 1949-; Ong, Charlson 1960- (Quezon City University of the Philippines Press, 2009)
An intervention into contemporary debates about nationalism and postcoloniality, this work attempts to locate the role of literary studies and the humanities in the age of globalization. It is informed by Deleuze and Guattari and Hardt and Negri, which are the critical lens through which dominant conceptions of nation, subjectivity, resistance, and analysis are interrogated. Through the book's analysis, subject and collective become sites in which multiple flows and forces interact and conflict, processes that are made legible in texts. Two acclaimed Filipino novels in English, Jessica Hagedorn's 'Dogeaters' and Charlson Ong's 'An Embarrassment of Riches,' are read as markers in the passage from the despotic national sovereignty of Martial Law to the flexible capitalist sovereignty of post-EDSA. Mapped by the trajectories of these texts, possibilities for resistance coalesce into a dynamic form of community that has yet to be imagined, the becoming-nation.
Introduction -- One. Striated and smooth nationhood -- Two. The logic of global capitalism -- Three. Lines of flight -- Four. Jessica Hagedorn's Dogeaters and the crisis of modernity -- Five. Charlson Ong's An embarrassment of riches and the passage to capitalist sovereignty -- Conclusion.
Keywords: Nation-state and globalization -- Philippines; Capitalism -- Social aspects -- Philippines; Capitalism -- Political aspects -- Philippines; Globalization -- Social aspects -- Philippines; Globalization -- Political aspects -- Philippines